Sodium Levels and Leukocyte Levels as Predictor Factors in Cases of Pediatric Perforated Appendicitis - Muhamad Givari (Indonesian Journal of Multidisciplinary Science, 2022)
Acute appendicitis is a surgical emergency that is often found in children with higher perforation rates at a younger age. Several examinations have been put forward as predictors of the incidence of appendix perforation. The purpose of this study was to determine the role of sodium and leukocytes as predictors of perforated appendicitis in children at RSUP Dr. M. Djamil, Padang.  This type of research is analytical with a cross-sectional study design. The study was conducted from August to October 2022 at RSUP Dr. M. Djamil Padang. The sample was taken by consecutive sampling with criteria aged 0-18 years and diagnosed with acute appendicitis at RSUP Dr. M. Djamil. In this study, a sample of 112 people with perforation occurred in 67 samples (60%). In the perforation group, most patients (55%) aged 6-11 years were male (67%), had hyponatremia laboratory results (91%) and leukocytosis laboratory results (86.5%) and underwent laparotomy procedures (57.2%). From the SPSS results, a significant difference was obtained between the incidence of hyponatremia in perforated and non-perforated appendicitis with a p-value of <0.001. The limit of the predictive value of sodium is ?134.5 mmol / L. Leukocytes were also found to be associated with perforated appendicitis with a p-value of <0.001 The limit of the predictive value of leukocytes is ? 14,025 cells / mm3.  There was a significant association between sodium and leukocyte levels and perforation incidence with predictive value limits of ?134.5 mmol/L and ? 14,025 cells/mm3, respectively.